The Application of the Aptitude Treatment Interaction Approach to the Mathematics Learning Outcomes of 8th Grade Students at SMP Negeri 5 X Koto Singkarak - Utami, Khurnia Budi; Yolanda, Nela Sari; Perdana, Dina Novarina; Suriani, Teni (The Future of Education Journal, 2025)
Based on initial observations and interviews conducted by the author with mathematics teachers and students of SMP Negeri 05 X Koto Singkarak, it was found that there is a lack of student interest in learning mathematics. Students find it difficult to understand mathematical concepts, which leads to a lack of motivation to engage in mathematics lessons. The learning process is still dominated by the teacher, with students simply receiving material from the teacher and then taking notes. This is further exacerbated by the students' lack of interest in doing exercises and homework. This type of research is experimental. The population of this study consists of 8th-grade students of SMP Negeri 05 X Koto Singkarak for the 2024/2025 academic year, which includes two classes. The sampling technique used is random sampling. The instruments used in this study are observation sheets related to the Aptitude Treatment Interaction (ATI) learning model and a learning achievement test. Based on the results of the research, after hypothesis testing and normality tests, the data analysis revealed that both sample classes were normally distributed and homogeneous at a significance level of α = 0.05. The results of the hypothesis test showed that t_calculated = 1.84 and t_table = 1.69, so t_calculated > t_table, meaning the hypothesis in this study is accepted. It can be concluded that: The mathematics learning outcomes of students using the Aptitude Treatment Interaction approach are better than the learning outcomes of students taught through conventional methods at the 8th-grade level of SMP Negeri 05 X Koto Singkarak for the 2024/2025 academic year.